2001
DOI: 10.1590/s1516-35982001000500012
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneidade de variâncias nos grupos genéticos formadores da raça Canchim

Abstract: RESUMO -Foram estimados componentes de variância para os pesos aos 365 e 550 dias de idade, de animais dos grupos genéticos, ½ Charolês-Zebu, ¾ Zebu-Charolês e 5/8 Charolês-Zebu, utilizados no processo de formação da raça Canchim, com o objetivo de verificar a ocorrência de variâncias heterogêneas entre os grupos genéticos e seu possível efeito na classificação dos animais, na avaliação genética. As estimativas foram obtidas utilizando-se o sistema MTDFREML. A estratégia utilizada para estimar os componentes d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
1
1
3
Order By: Relevance
“…In general, the direct heritability estimates for the weight traits obtained in this work were lower than those related in literature for similar traits (Eler et al 1995;Gianlorenço et al, 2003;Meyer, 1992;Oliveira et al, 2001;Toral et al, 2008 and2009), but with data from Zebu, European or crossbred European × Zebu. Similar tendencies were observed for the heritability estimates of average daily weight gain from birth to weaning and from weaning to 365 days (Alencar et al, 2005;Castor-Pereira et al, 2007).…”
Section: Resultscontrasting
confidence: 82%
“…In general, the direct heritability estimates for the weight traits obtained in this work were lower than those related in literature for similar traits (Eler et al 1995;Gianlorenço et al, 2003;Meyer, 1992;Oliveira et al, 2001;Toral et al, 2008 and2009), but with data from Zebu, European or crossbred European × Zebu. Similar tendencies were observed for the heritability estimates of average daily weight gain from birth to weaning and from weaning to 365 days (Alencar et al, 2005;Castor-Pereira et al, 2007).…”
Section: Resultscontrasting
confidence: 82%
“…A existência de variâncias heterogêneas foi observada por Oliveira et al (3) nos grupos genéticos participantes da formação da raça Canchim e por Urioste et al (4) na raça Holandesa.…”
Section: Introductionunclassified
“…WINKELMAN & SCHAEFFER (1988) reported that the effect of the heterogeneity of variances is important for the selection of cows, young sires, and calves because these animals have records within a single herd/environment and, thus, their evaluations can be affected by differences in environmental variances. The effects of sex, farm, and animal age, for example, can be classified as sources of heteroscedasticity; in the case of crossbred populations, the composition of the breed and its genetic interactions can also be considered causes of heteroscedasticity (CARDOSO et al, 2005;OLIVEIRA et al, 2001;RODRÍGUEZ-ALMEIDA et al, 1995).…”
Section: Resultsmentioning
confidence: 99%